Medical education. Modern methods and alternative methods to animal procedures - PAPALOIS (Α.Ε. ΠΑΠΑΛΟΗΣ) A. E. (Journal of the Hellenic Veterinary Medical Society, 2017)
The purpose of medical education, as well as of skills for medical doctors and veterinary doctors (continuing medical education and professional development), is to encourage decision-makers and healthcare professionals to ensure appropriate mechanisms for safe medical care. Medical education has been affected by several technological and financial developments. The rapidly evolving technology and knowledge challenged traditional educational concepts. Also alternative methods for training are in use in many centres worldwide (patient simulators, cadaver tissues, robotics, participation in daily surgery and other).